The role of the teacher in a pediatric oncology hospital classroom. - Reyes Laredo, Francisco (2018)
This study show the results of a work of indirect observation of the task of the teachers at the hospital classrooms in the area of pediatric oncology. The attendance to different sessions of the classroom, as well as the interview to the teacher in charge, has allowed us to carry out a detailed analysis of this unique school environment. Likewise, this work is completed work with a bibliographical revision that has facilitated the exhaustive knowledge of the normative context for this type of school classrooms and of the pedagogical and psychological aspects to be considered in the teaching-learning process.